ripley's rbi fact or fiction? bureau of investigation: the dragon's triangle - Publishing Riley's; Riley's Publishing (United States Ripley's Publishing, 2010)
The Dragon's Triangle by Kay Wilkins (published by Ripley's Publishing, 2010) is a fictional middle-grade mystery novel. It follows the RBI (Ripley Bureau of Investigation) agents tracking a sea monster off the Japanese coast, blending the real, legendary "Devil's Sea" mystery with a fictionalized, thrilling adventure tailored for younger readers
English